From pseudohypoparathyroidism to inactivating PTH/PTHrP signalling disorder (iPPSD), a novel classification proposed by the EuroPHP network. Issue 6 (December 2016) - Thiele, Susanne; Mantovani, Giovanna; Barlier, Anne; Boldrin, Valentina; Bordogna, Paolo; De Sanctis, Luisa; Elli, Francesca M; Freson, Kathleen; Garin, Intza; Grybek, Virginie; Hanna, Patrick; Izzi, Benedetta; et al.
Abstract : Objective: Disorders caused by impairments in the parathyroid hormone (PTH) signalling pathway are historically classified under the term pseudohypoparathyroidism (PHP), which encompasses rare, related and highly heterogeneous diseases with demonstrated (epi)genetic causes. The actual classification is based on the presence or absence of specific clinical and biochemical signs together with an in vivo response to exogenous PTH and the results of an in vitro assay to measure Gsa protein activity. However, this classification disregards other related diseases such as acrodysostosis (ACRDYS) or progressive osseous heteroplasia (POH), as well as recent findings of clinical and genetic/epigenetic background of the different subtypes. Therefore, the EuroPHP network decided to develop a new classification that encompasses all disorders with impairments in PTH and/or PTHrP cAMP-mediated pathway. Design and methods: Extensive review of the literature was performed. Several meetings were organised to discuss about a new, more effective and accurate way to describe disorders caused by abnormalities of the PTH/PTHrP signalling pathway. Results and conclusions: After determining the major and minor criteria to be considered for the diagnosis of these disorders, we proposed to group them under the term 'inactivating PTH/PTHrP signalling disorder' (iPPSD). This terminology: (i) defines the common mechanism responsible for all diseases; (ii) does not require a confirmed genetic defect; (iii) avoids ambiguous terms like 'pseudo' and (iv) eliminates the clinical or molecular overlap between diseases. We believe that the use of this nomenclature and classification will facilitate the development of rationale and comprehensive international guidelines for the diagnosis and treatment of iPPSDs.